Back Cover: Probing the Backbone Topology of DNA: Synthesis and Properties of 7′, 5′‐Bicyclo‐DNA (Chem. Eur. J. 33/2017). Issue 33 (10th April 2017) - Evéquoz, Damien; Leumann, Christian J.
Abstract : Structural metamorphosis by conformational restriction and a shift of the point of attachment of the phosphodiester linkage transforms DNA from the already known 3′, 5′‐bicyclo(bc)‐DNA into the novel 7′, 5′‐bc‐DNA. This DNA analogue forms an independent Watson–Crick base‐pairing system with similar duplex stabilities compared to natural DNA that only very weakly cross‐pairs with natural DNA. It thus shows promising features for a synthetic genetic system (xeno nucleic acid). More information can be found in the Full Paper by D. Evéquoz and C. J. Leumann onpage 7953 .